PENGARUH IMPLEMENTASI SISTEM INFORMASI MANAJEMEN RUMAH SAKIT TERHADAP KUALITAS PELAYANAN RUANG BERSALIN DAN NIFAS DI RUMAH SAKIT UMUM DAERAH GUNUNGSITOLI KABUPATEN NIAS TAHUN 2020 - polem, cut mawaddah (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Hospitals require the implementation of a management information system that can be enable fast and accurate in data processing to create high quality service. Zeithmal's service quality theory has 5 indicators: Tangibles, Realibility, Responsiveness, Assurance, Emphaty, Manual data processing has many drawbacks which are time consuming and data inaccurate due to the possibility of major errors. The importance of the Hospital Management Information System has been set forth in the Minister of Health Regulation No. 82 of 2013 on Hospital Management Information System. According to Edwards III, there are four factors that influence implementation: communication, resources, attitude (disposition), and bureaucratic structure . Sampling use total sampling technique. The sample taken in this study was 30 people. The survey instrument used the questionnaire. There is the influence of Implementation of Hospital Management Information System communication on the quality of maternity Room and delivery Room services at General Hospital of Gunungsitoli Regency amounted to 12 (40%). The influence of resources amounted to 13 (43.3%), The influence of attitude / Disposition Implementation amountedt to 43.3%, the influence of Bureaucratic Structural Implementation amounted to 15 (50%), the influence of Hospital Management Information System Implementation on quality Maternity Room and Delivery Room service at Gunungsitoli Regional General Hospital of Nias regency was significant in terms of quality of service, with p <0.05.